Unusual Popping Sound as an Indicator of Missed Root Canal: A Case Report - Aminsobhani, Mohsen; Marvi, Mohammad; MahjourianQomi, Reza (Iranian Endodontic Journal, 2024)
The patients with unusual symptoms present a diagnostic challenge for clinicians and may lead to misdiagnoses and inappropriate or unnecessary treatments. Endodontic diseases can present with a variety of symptoms, and it is possible for odontogenic pain to resemble non-odontogenic pain, which can complicate treatment due to the distinct management plans of the two conditions. This report details the successful management of vague pain, and popping sensations in the left maxilla triggered by cold exposure. Previous clinicians were unable to identify the pain's origin, leading to unnecessary treatments. A clinical examination, and cone-beam computed tomography evaluation revealed the presence of a missed second mesiobuccal root canal. The canal was located using an operating microscope and ultrasonics. Non-surgical endodontic retreatment was completed in two visits, successfully. This report highlights the critical importance of identifying the diverse symptoms that may arise from endodontic origin, as these can complicate clinical diagnosis.